Trinidad Carnival - (:unkn) unknown (T.Geddes Grant (Trinidad) Ltd, Trinidad, West Indies, 2009)
A masquerader portraying a colourful Fancy Sailor. Affixed to the postcard is a 20 cents Trinidad and Tobago postage stamp.
Colour:Coloured; Style:Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Carnival; Carnival costumes; Sailors